Analisis Pengaruh Profitabilitas, Solvabilitas, Dan Nilai Pasar Terhadap Return Saham Pada Perusahaan Go Publik Di Bursa Efek Indonesia (Studi Pada Perusahaan Jasa Sub Sektor Restoran, Hotel Dan Pariwisata) - Sisilia Maria Parinusa (JFRES Journal of Fiscal and Regional Economy Studies, 2020)
Financial ratios are employed in this research to measure the influence of profitability, solvency and price to book value on stock return in restaurant, hotel and tourism companies which are listed on Indonesia Stock Exchange from period 2014 – 2018. The objectives of this study was to provide empirical findings whether profitability, solvency and price to book value have a significant influence on stock return. Multiple linear regression analysis was used to identify the strength of the effect of Return On Assets (ROA), Return On Equity (ROE), Debt to Equity Ratio (DER) and Price to Book Value (PBV) on stock return simultaneously and partially.The result of this study indicates that simultaneously ROA, ROE, DER and PBV have a significant effect on stock return and there is a positive significant effect of return on assets on stock return. Whereas price to book value has a negative significant effect on stock return in restaurant, hotel and tourism companies listed on IDX. Furthermore, return on equity and debt to equity ratio have no significant impact on stock return. Among the predictor variables, the data analysis showed that return on assets is the most important predictor variables in this regression model.